Teen Titans. The complete fifth season [videorecording (DVD)] (DC Comics kids collection., 2008)
The teen scene is over for these adolescent phenoms--Robin, Starfire, Cyborg, Beast Boy and Raven--as they launch into a feud with the ultimate team of villains: The Brotherhood of Evil. Led by criminal mastermind Brain, this motley group--Madam Rouge, Monsieur Mallah and General Immortus--plots to rid the world of every superhero. One by one, they take out honorary Titans like Wildebeest and Hotspot, escalating the vendetta into a global war that ends with the unthinkable. It's up to Beast Boy to perform his most amazing transformation, or it will certainly be the end of the Titans forever.